Solid polymer electrolyte adhesive film for electrochromic device as well as preparation method and application of solid polymer electrolyte adhesive film
By introducing lithium salt and water into the ethylene-vinyl acetate copolymer and processing under constant temperature and humidity conditions, a solid polymer electrolyte gel film with high room temperature ionic conductivity was prepared, which solved the problems of environmental pollution and insufficient conductivity during the material preparation process in the prior art, and achieved high-performance electrochromic device materials.
Patent Information
- Application Number
- CN202411739146.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The existing polymer electrolyte materials rely on a large amount of organic solvents during the preparation process, resulting in environmental pollution and degradation of device mechanical properties, and the room temperature ionic conductivity is not sufficient to meet the needs of electrochromic devices.
By heating and premixing the ethylene-vinyl acetate copolymer with lithium salt additives and rolling under constant temperature and humidity conditions, a solid polymer electrolyte glue film with high room temperature ionic conductivity was prepared.
It achieves high room temperature ionic conductivity (3.43×10-4S/cm), and has excellent optical transmittance, thermal stability and mechanical properties, meets the application requirements of electrochromic devices, and avoids the use of organic solvents, achieving an environmentally friendly and pollution-free preparation process.
Smart Images

Figure CN119505744A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer films, and in particular relates to a solid polymer electrolyte film for an electrochromic device and a preparation method and application thereof. Background Art
[0002] WO3-NiO-based electrochromic devices can actively adjust visible and infrared light under small stimulation of external electric field (1~3 V), and have attracted more attention due to their great application potential in diversified fields, such as smart windows for energy-saving buildings. Usually, complementary electrochromic devices have two symmetrical conductive layers, two electrochromic layers and an electrolyte layer from the outside to the inside.
[0003] So far, there are two main configurations for building such WO3-NiO devices based on the assembly process. One is the so-called "layer-by-layer" configuration, that is, the above five layers are deposited successively on a single substrate by magnetron sputtering to form a stacked structure. Unfortunately, this stacked structure configuration is affected by the extremely thin (<100 nm) inorganic electrolyte layer. Therefore, during the sputtering process, inevitable defects such as small pinholes, impurity particle retention, etc. will be generated in such a thin layer. Through these defects, the two electrodes are in direct contact, which then leads to a short circuit and destroys the stable operation of the device. The other is the so-called "laminated" configuration, in which the individual components of substrate / ITO / WO3 and substrate / ITO / NiO are first produced by magnetron sputtering, and then laminated with a micron-thick transparent polymer electrolyte as an interlayer film to form an assembled device. In this laminated configuration, the application of such a thick electrolyte can fundamentally eliminate the adverse effects of defects caused by thinner electrolytes on the device, and also make the device assembly more efficient. In the laminated WO3-NiO ECD, the polymer electrolyte is an important factor determining the response speed, transparency and mechanical strength, and therefore should have comprehensive properties such as high ionic conductivity, wide potential window, thermal stability, chemical and electrochemical stability, high optical transparency, ruggedness, low cost and environmental friendliness.
[0004] At present, the existing polymer electrolytes are mainly divided into two categories: gel electrolytes containing some plasticizers or other organic solvents and solid electrolytes without any plasticizers or other organic solvents. Electrochimica Acta , 2022, 432, 141216 discloses a method for preparing a gel polymer electrolyte by adding ionic liquid [BMIM][TFSI] and lithium salt LiTFSI to PVDF-HFP, PMMA and PEG; J. Mater. Chem. A 2023, 11, 8939 published a gel polymer electrolyte system composed of PVDF, LiClO4, PC, and UV curing agent. In terms of solid electrolytes, Adv. Funct. Mater. 2023, 33, 2214417 disclose a method for forming a solid polymer electrolyte by adding LiTFSI after cross-linking reaction of PVB and KH560. However, in the process of preparing the polymer film, a large amount of organic solvent (dimethylacetamide) is required to assist the film formation. From the public data, although the above two systems can obtain relatively high ionic conductivity (>1.0×10 -4 S / cm), but there are still the following shortcomings: (1) For gel electrolytes, the presence of a large amount of liquid solvent medium in the system will seriously lead to a decrease in the mechanical properties of the polymer film, making it difficult to achieve a strong bond with the glass, affecting the safety performance of the laminated glass. In addition, it also brings about the flammability problem of the device. These solvents are highly flammable and not only cannot prevent the spread of flames, but can also accelerate the combustion process. (2) For solid electrolyte materials, since the preparation of the polymer film relies on a large amount of organic solvents (dimethylacetamide) to assist in film formation, a large amount of organic volatiles are emitted during the preparation process, causing air pollution problems. Therefore, the production process of this material is not environmentally friendly. On the other hand, ethylene-vinyl acetate copolymer (EVA) used for photovoltaic module encapsulation has good optical transparency, low-temperature flexibility and other properties. As a laminated polymer material, it has been maturely used in the photovoltaic field for many years. However, when applied to polymer electrolyte materials, its room temperature ionic conductivity is low (usually less than 10 -8 S / cm), which cannot meet the requirements of electrochromic devices operating at room temperature. Summary of the invention
[0005] The main purpose of the present invention is to provide a solid polymer electrolyte film for electrochromic devices and its preparation method and application, so as to overcome the shortcomings of the prior art.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes: The embodiment of the present invention provides a method for preparing a solid polymer electrolyte film for an electrochromic device, which comprises: premixing ethylene-vinyl acetate copolymer and lithium salt additive by heating to obtain a first solid product; Furthermore, the first solid product is subjected to roller pressing and constant temperature and humidity treatment to obtain a solid polymer electrolyte film for an electrochromic device.
[0007] An embodiment of the present invention also provides a solid polymer electrolyte film for an electrochromic device prepared by the aforementioned preparation method, wherein the solid polymer electrolyte film is prepared from at least ethylene-vinyl acetate copolymer, water, and a lithium salt additive, and the surface of the solid polymer electrolyte film has a mesh-like wrinkled structure.
[0008] The embodiment of the present invention further provides an electrochromic device, which at least includes the aforementioned solid polymer electrolyte film.
[0009] An embodiment of the present invention further provides an electrochromic smart window, which at least includes the aforementioned solid polymer electrolyte film or electrochromic device.
[0010] Compared with the prior art, the present invention has the following beneficial effects: (1) The solid polymer electrolyte film prepared by the present invention has excellent ionic conductivity, and the room temperature ionic conductivity is as high as 3.43×10 -4 S / cm; (2) The solid polymer electrolyte film prepared by the present invention has the properties of colorless transparency, excellent optical transmittance (>90%), no haze, etc., and can meet the visual requirements of application scenarios such as electrochromic smart windows; (3) The solid polymer electrolyte film prepared by the present invention has a temperature resistance of >200°C, which meets the temperature requirements for device assembly and safe operation; (4) The tensile strength of the solid polymer electrolyte film prepared by the present invention can reach up to 1.61 MPa, which meets the requirements for safe operation of the device; (5) The solid polymer electrolyte film prepared by the present invention can be used to assemble high-quality WO3-NiO electrochromic devices using existing lamination processes; at the same time, the prepared device has fast switching speed; excellent coloring and fading stability; excellent cycle stability (it can still work normally after 10,000 cycles without failure phenomena such as bubbles and shedding), outstanding visible light and near-infrared light modulation capabilities, etc.; (5) The present invention does not introduce any organic solvent in the process of preparing the solid polymer electrolyte film, which is green, environmentally friendly and pollution-free; (6) The solid polymer electrolyte film preparation process provided by the present invention can easily realize the preparation of electrolyte films with larger areas. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0012] Figure 1 is the XRD spectrum of the polymer solid electrolyte film prepared in Example 1 of the present invention; Figure 2 is a surface SEM photograph of the polymer solid electrolyte film of Example 1 of the present invention; Figure 3 is a thermogravimetric analysis curve of the polymer solid electrolyte film prepared in Example 1 of the present invention; Figure 4 is a comparison chart of the optical transmittance of the polymer solid electrolyte film prepared in Example 1 of the present invention and the ultra-white glass; Figure 5 is a photograph of the appearance of the polymer solid electrolyte film prepared in Example 1 of the present invention; Figure 6 The 20×25 cm 2 Appearance photo of large-scale polymer solid electrolyte film; Figure 7 is a comparative bar graph of room temperature ionic conductivity of the polymer solid electrolyte membranes prepared in Example 1 of the present invention and Comparative Example 1; Figure 8 is a tensile stress-strain curve diagram of the polymer solid electrolyte film prepared in Example 1 of the present invention and Comparative Example 1; Figure 9a-9b The 20×20 cm 2 Photos of large-scale electrochromic devices in the colored and faded states. DETAILED DESCRIPTION
[0013] In view of the defects of the prior art, the inventors of this case have proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution mainly introduces a small amount of water into the ethylene-vinyl acetate copolymer electrolyte through constant temperature and humidity treatment, so as to achieve the purpose of improving the room temperature ionic conductivity without changing the visible light transmittance, mechanical, thermal and other properties of the film.
[0014] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0015] Specifically, as one aspect of the technical solution of the present invention, a method for preparing a solid polymer electrolyte film for an electrochromic device includes: premixing ethylene-vinyl acetate copolymer and lithium salt additive by heating to obtain a first solid product; Furthermore, the first solid product is subjected to roller pressing and constant temperature and humidity treatment to obtain a solid polymer electrolyte film for an electrochromic device.
[0016] In some preferred embodiments, the preparation method specifically comprises: premixing the ethylene-vinyl acetate copolymer and the lithium salt additive by heating at 100-150° C. for 0.2-1 h to obtain a first solid product.
[0017] Furthermore, the molecular structure of the ethylene-vinyl acetate copolymer is .
[0018] Furthermore, the ethylene-vinyl acetate copolymer (EVA) is a random copolymer.
[0019] Furthermore, the content of vinyl acetate (VA) in the ethylene-vinyl acetate copolymer is 12-44 wt%.
[0020] Furthermore, the melt index of the ethylene-vinyl acetate copolymer is 8 to 52 g / 10 min.
[0021] Further, the lithium salt additive includes any one or more combinations of lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, lithium trifluoromethanesulfonate, lithium hexafluorophosphate, and lithium tetrafluoroborate, but is not limited thereto.
[0022] Furthermore, the mass ratio of the ethylene-vinyl acetate copolymer to the lithium salt additive is 100:(20-200).
[0023] In some preferred embodiments, the preparation method specifically includes: placing the first solid product in a double-roll mill and rolling and mixing at 50-100°C for 0.2-1h, and adding a crosslinking agent and a co-crosslinking agent during rolling and mixing to obtain a first film.
[0024] In some preferred embodiments, the preparation method specifically includes: placing the first film in a constant temperature and humidity environment with a temperature of 30-80°C and a relative humidity of 10-50% for 0.2-1h to obtain a solid polymer electrolyte film for an electrochromic device.
[0025] Further, the cross-linking agent includes any one or more combinations of tert-butyl peroxide-2-ethylhexanoate, 3-2-tert-butyl peroxide, tert-diisopropylbenzene peroxide, 2,5-dihydroperoxide, tert-butyl peroxide-3,3,5-trimethylcyclohexanoate, tert-butyl peroxide-laurate, tert-butyl peroxide-2-ethylhexyl carbonate, and 4-methylbenzoyl peroxide, and is not limited thereto.
[0026] Further, the auxiliary cross-linking agent includes any one or more combinations of trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane triacrylate, ethoxylated trimethylolpropane trimethacrylate, NN-m-phenyl bismaleimide, 1,2-polybutadiene, diallyl phthalate, triallyl isocyanate, and triallyl cyanate, and is not limited thereto.
[0027] In some more specific embodiments, the method for preparing the solid polymer electrolyte film for the electrochromic device comprises the following steps: S1. Premix ethylene-vinyl acetate copolymer and lithium salt additive on a heating table at 100°C to 150°C for 0.2 to 1 h to obtain an opaque white rubber block; S2. The opaque white rubber block prepared in S1 was placed between the two rolls of a double-roll mill and rolled and mixed at 50 to 100 ° C for 0.2 to 1 h, and a cross-linking agent and a co-cross-linking agent were added during the rolling and mixing to obtain a uniform and transparent film; S3. The uniform and transparent film obtained in S2 is placed in a constant temperature and humidity chamber at a temperature of 30-80°C and a relative humidity of 10-50% for 0.2-1h to finally obtain a solid polymer electrolyte film.
[0028] The solid polymer electrolyte membrane provided by the above scheme is used, water is used as an additive, and water and Li + The coordination interaction weakens the Li + The coordination effect with the ester carbonyl C=O in ethylene-vinyl acetate copolymer reduces the crystallinity of the solid polymer electrolyte film, thereby promoting the Li + The rapid conduction of the material improves the room temperature ionic conductivity while having good optical, thermal and mechanical properties. The room temperature ionic conductivity obtained is as high as 3.43×10 -4 S / cm; to meet the application requirements of electrochromic devices.
[0029] At the same time, the solid polymer electrolyte film has good thermal stability and mechanical properties. It can withstand the process temperature of device lamination (130°C) and the maximum operating temperature of the device during operation (80°C). Its tensile strength can reach up to 1.61 MPa.
[0030] In summary, the solid polymer electrolyte film obtained by the technical solution of the present invention has excellent optical, thermal and mechanical properties, and has a maximum -4 The room temperature ionic conductivity of S / cm can meet the requirements of electrochromic devices, and at the same time, can meet the visual requirements of application scenarios such as electrochromic smart windows.
[0031] Another aspect of an embodiment of the present invention also provides a solid polymer electrolyte film for an electrochromic device prepared by the aforementioned preparation method, wherein the solid polymer electrolyte film is made of at least ethylene-vinyl acetate copolymer, water, and a lithium salt additive, and the surface of the solid polymer electrolyte film has a mesh-like wrinkled structure.
[0032] In some preferred embodiments, the solid polymer electrolyte membrane is made of ethylene-vinyl acetate copolymer, water, a cross-linking agent, a co-cross-linking agent and a lithium salt additive; wherein the mass ratio of the ethylene-vinyl acetate copolymer, water, a cross-linking agent, a co-cross-linking agent and a lithium salt additive is 100:(0.2~2):(0~2):(0~4):(20~200).
[0033] In some preferred embodiments, the thickness of the solid polymer electrolyte film is 30-300 μm.
[0034] In some preferred embodiments, the size of the solid polymer electrolyte film can be 20×25 cm 2 .
[0035] Another aspect of the embodiments of the present invention further provides an electrochromic device, which at least includes the aforementioned solid polymer electrolyte film.
[0036] Another aspect of the embodiments of the present invention further provides an electrochromic smart window, which at least includes the aforementioned solid polymer electrolyte film or electrochromic device.
[0037] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.
[0038] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.
[0039] Example 1 This embodiment provides a preparation process of a solid polymer electrolyte film capable of conducting Li ions, and the specific steps are as follows: S1. 10 parts of ethylene-vinyl acetate copolymer (VA content of 40 wt.%) and 12 parts of lithium bis(trifluoromethanesulfonyl imide) were pre-mixed on a heating table at 130°C for 50 min to obtain an opaque white rubber block; S2. The opaque white rubber block prepared in S1 was placed between the two rolls of a double-roll mill and rolled and mixed at 75°C for 40 min to obtain a uniform transparent film; S3. The uniform and transparent film obtained in S2 is placed in a constant temperature and humidity chamber at a temperature of 50° C. and a relative humidity of 25% for 1 hour to finally obtain the polymer solid electrolyte film.
[0040] Example 2 The difference between this embodiment and embodiment 1 is that the relative humidity of the constant temperature and humidity treatment is 15%. After testing, the optical transmittance of the film is 90%, the tensile strength is 1.52 MPa, and the ionic conductivity is 1.18×10 -4 S / cm.
[0041] Example 3 The difference between this embodiment and embodiment 1 is that the relative humidity of the constant temperature and humidity treatment is 35%. After testing, the optical transmittance of the film is 90%, the tensile strength is 1.45 MPa, and the ionic conductivity is 4.56×10 -4 S / cm.
[0042] Example 4 The difference between this embodiment and embodiment 1 is that 0.2 parts of dicumyl peroxide, a crosslinking agent, is added during the rolling mixing on the open mill, and no constant temperature and humidity treatment is performed. After testing, the optical transmittance of the film is 90%, and the ionic conductivity is 2.81×10 -5 S / cm.
[0043] Example 5 The difference between this embodiment and embodiment 1 is that 0.2 parts of dicumyl peroxide as a crosslinking agent and 0.5 parts of ethoxylated trimethylolpropane triacrylate as a co-crosslinking agent are added during the rolling mixing on the open mill, and no constant temperature and humidity treatment is performed. After testing, the optical transmittance of the film is 90%, and the ionic conductivity is 1.11×10 -6 S / cm.
[0044] Comparative Example 1 The difference between this comparative example and Example 1 is that constant temperature and humidity treatment is not performed, and the other aspects are the same.
[0045] Performance characterization: 1. Phase structure and surface morphology: X-ray diffractometer (XRD) was used to observe the phase structure of the film; scanning electron microscope (SEM) was used to observe the surface morphology of the film.
[0046] 2. Optical properties: The optical properties (light transmittance) of the films were measured using a UV-visible spectrophotometer.
[0047] 3. Thermogravimetric analysis (TGA) was used to characterize the thermal stability of the film.
[0048] 4. Use 1kN universal material testing machine to measure mechanical properties.
[0049] 5. Use an electrochemical workstation to measure the electrochemical properties of the film.
[0050] The above-mentioned analytical equipment or method is used to compare the performance of Example 1 and Comparative Example 1 to further illustrate the superiority and advancement of the present invention.
[0051] Figure 1 The XRD spectra of Example 1 and Comparative Example 1 are given. It can be seen from the figure that compared with Comparative Example 1, Example 1 has a broader EVA diffraction peak, indicating that Example 1 has a lower degree of crystallinity and an improved amorphous region, which is beneficial to the segment migration of the main chain and achieves a higher room temperature ionic conductivity.
[0052] Figure 2 The SEM photo of Example 1 is given. Figure 2 It can be seen that the surface of the film of Example 1 has uniform mesh wrinkles, which is conducive to the discharge of air during the lamination process, thereby ensuring close adhesion between the polymer solid electrolyte and the electrochromic active layer, and further contributing to the formation of a high-quality laminated electrochromic device.
[0053] Figure 3 The thermal weight loss curve of the adhesive film prepared in Example 1 at 30~220°C is given. It can be seen that the adhesive film has almost no weight loss, which indicates that the adhesive film has high thermal stability and can not only withstand the process temperature of device lamination (130°C), but also withstand the maximum operating temperature (80°C) of the device during operation.
[0054] Figure 4 The optical transmittance spectrum of the polymer solid electrolyte film prepared in Example 1 is given, from which it can be seen that the visible light transmittance of the film exceeds 90%, which is comparable to the optical transmittance of ultra-white glass (the transmittance is generally greater than 91.5%).
[0055] Figure 5 The appearance morphology of the film is given, and it can be seen that it is colorless and transparent with clear boundaries and no haze, which can meet the visual requirements of application scenarios such as electrochromic smart windows.
[0056] Figure 6 20×25 cm prepared in Example 1 of the present invention 2 Appearance photo of large-size polymer solid electrolyte film.
[0057] Figure 7 The room temperature ionic conductivity of the polymer solid electrolyte membrane prepared in Example 1 and Comparative Example 1 is given. Compared with Comparative Example 1, the room temperature ionic conductivity of Example 1 is increased from 0.79×10 -4 S / cm increased to 3.43×10 -4S / cm. Obviously, this embodiment significantly improves the room temperature ionic conductivity of the EVA-based polymer solid electrolyte.
[0058] Figure 8 The tensile stress-strain curves of the polymer solid electrolyte films prepared in Example 1 and Comparative Example 1 are given. It can be seen from the figure that the tensile strength of Comparative Example 1 is 1.48 MPa, while the tensile strength of Example 1 is 1.61 MPa. The present invention improves the mechanical properties of the polymer solid electrolyte.
[0059] Figure 9a-9b The 20×20 cm prepared in Example 1 of the present invention 2 Photos of large-scale electrochromic devices in the colored and faded states.
[0060] The properties of the films prepared in Examples 1-5 and Comparative Examples 1-2 are shown in Table 1.
[0061] Table 1 Properties of the films prepared in Examples 1-5 and Comparative Examples 1-2
[0062] Note: - indicates not tested.
[0063] In summary, Example 1 is the best embodiment of the present invention. The EVA polymer solid electrolyte obtained by constant temperature and humidity treatment at 50°C and relative humidity of 25% has a room temperature ionic conductivity of up to 3.43×10 -4 S / cm, and can have better tensile strength.
[0064] Specifically, the light transmittance of Examples 1 and 2 is 90%, indicating that a material with stable optical properties can be obtained by adopting the technical solution of the present invention.
[0065] It can be seen from the results of Example 1 and Comparative Example 1 that, under the same other conditions, the polymer solid electrolyte prepared by Example 1 after constant temperature and humidity treatment at 50°C and relative humidity of 25% significantly improves the room temperature ionic conductivity, from 0.79×10 -4 S / cm increased to 3.43×10 -4 S / cm; the tensile strength is also increased from 1.48 MPa to 1.61 MPa. Obviously, the present invention can improve the room temperature ionic conductivity and mechanical properties of the polymer solid electrolyte through constant temperature and humidity treatment.
[0066] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0067] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.
Claims
1. A method for preparing a solid polymer electrolyte film for an electrochromic device, characterized in that: include: premixing ethylene-vinyl acetate copolymer and lithium salt additive by heating to obtain a first solid product; Furthermore, the first solid product is subjected to roller pressing and constant temperature and humidity treatment to obtain a solid polymer electrolyte film for an electrochromic device.
2. The preparation method according to claim 1, characterized in that: Specifically include: The ethylene-vinyl acetate copolymer and the lithium salt additive are premixed by heating at 100-150° C. for 0.2-1 hour to obtain a first solid product.
3. The preparation method according to claim 2, characterized in that: The molecular structure of the ethylene-vinyl acetate copolymer is ; and / or, the content of vinyl acetate in the ethylene-vinyl acetate copolymer is 12-44 wt %; And / or, the melt index of the ethylene-vinyl acetate copolymer is 8 to 52 g / 10 min; And / or, the lithium salt additive includes any one or more combinations of lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, lithium trifluoromethanesulfonate, lithium hexafluorophosphate, and lithium tetrafluoroborate; And / or, the mass ratio of the ethylene-vinyl acetate copolymer to the lithium salt additive is 100:(20-200).
4. The preparation method according to claim 1, characterized in that: Specifically include: The first solid product is placed in a double-roll open mill and roll-mixed at 50-100° C. for 0.2-1 h, and a cross-linking agent and an auxiliary cross-linking agent are added during the roll-mixing to obtain a first adhesive film.
5. The preparation method according to claim 4, characterized in that: Specifically include: The first adhesive film is placed in a constant temperature and humidity environment with a temperature of 30-80° C. and a relative humidity of 10-50% for 0.2-1 h to obtain a solid polymer electrolyte adhesive film for an electrochromic device.
6. The preparation method according to claim 4, characterized in that: The crosslinking agent includes any one or more of tert-butyl peroxide-2-ethylhexanoate, 3-2-tert-butyl peroxide, tert-diisopropylbenzene peroxide, 2,5-dihydroperoxide, tert-butyl peroxide-2-ethylhexanoate, tert-butyl laurate peroxide, tert-butyl peroxide-2-ethylhexyl carbonate, and 4-methylbenzoyl peroxide. And / or, the auxiliary cross-linking agent includes any one or more combinations of trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane triacrylate, ethoxylated trimethylolpropane trimethacrylate, NN-m-phenyl bismaleimide, 1,2-polybutadiene, diallyl phthalate, triallyl isocyanate, and triallyl cyanate.
7. A solid polymer electrolyte film for an electrochromic device prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The solid polymer electrolyte film is made of at least ethylene-vinyl acetate copolymer, water and lithium salt additives, and the surface of the solid polymer electrolyte film has a mesh-like wrinkled structure.
8. The solid polymer electrolyte membrane according to claim 7, characterized in that: The solid polymer electrolyte film is made of ethylene-vinyl acetate copolymer, water, a cross-linking agent, a co-cross-linking agent and a lithium salt additive; wherein the mass ratio of the ethylene-vinyl acetate copolymer, water, a cross-linking agent, a co-cross-linking agent and a lithium salt additive is 100: (0.2-2): (0-2): (0-4): (20-200); And / or, the thickness of the solid polymer electrolyte film is 30-300 μm.
9. An electrochromic device, characterized in that: At least comprises the solid polymer electrolyte membrane as described in claim 7 or 8.
10. An electrochromic smart window, characterized in that: At least comprising the solid polymer electrolyte film according to any one of claims 7-8 or the electrochromic device according to claim 9.
Citation Information
Patent Citations
Acetic acid vinyl ester-acrylic ester copolymer basis solid polymer electrolyte and film
CN101130587A
Manufacturing of high-transmittance flexible electrochromic film
CN108931873A
Preparation and application of high-cycling performance quasi-solid electrochromic PVB electrolyte film
CN110703528A
Method for preparing all-solid-state polymer electrolyte membranes in batches by adopting double-roller plasticator
CN111224152A
Polymer solid electrolyte adhesive film for electrochromic device as well as preparation method and application of polymer solid electrolyte adhesive film
CN116082776A